Shear property characterization of aramid paper and its application to the prediction of honeycomb behaviors. (15th December 2020) - Yang, Weichao; Zhang, Xufeng; Yang, Kuijian; Pan, Bing; Fei, Binjun; Yi, Xiaosu; Chen, Yuli
Highlights: The shear properties of aramid paper are characterized for the first time.. Characterizing shear properties of paper makes the prediction of honeycombs better. The failure mode map of paper honeycombs subjected to complex loads is obtained. Abstract: Aramid paper honeycomb cores have been widely used in lightweight structures. However, shear properties of aramid paper can hardly be obtained accurately due to the shear buckling of the paper. Therefore, we make the paper into a laminate to prevent buckling and apply the v-notched beam test method to the laminate to obtain the in-plane shear properties of aramid paper. The shear strength and failure strain of aramid paper are characterized experimentally for the first time. The properties are then used in finite element simulations to study the shear behaviors of paper honeycombs and the good agreement with the experimental results indicates the validity of the shear properties. Furthermore, the failure mode map of the paper honeycomb subjected to combined shear and compressive loads is obtained, which presents the importance of the accurate characterization on the shear properties of the paper. This characterization method can also be applied to other types of paper.